A phenomenological approach to ionic mass transfer at rotating disc electrodes with a hanging column of electrolyte solution - Elsner, Cecilia Inés (1993)
Experimental data for the behaviour of a rotating disc electrode with a hanging electrolyte column of varying height are presented. A correlation involving the limiting current density, the rotation speed, and the physicochemical properties of the solution is established. The macroscopic effective copper electrodeposit thickness distribution is determined. Results obtained for different electrode designs are discussed in terms of an additional flow of reactant, and an apparent change in the effective electrode area caused by liquid column contraction. From the results the most suitable experimental conditions for the application of the rotating disc electrode with a hanging column of electrolyte to electrochemical kinetic studies can be found.